Influence of nanofluids on parallel flow square microchannel heat exchanger performance - Mohammed H.A.; Bhaskaran G.; Shuaib N.H.; Abu-Mulaweh H.I. (2023)
The effects of using various types of nanofluids and Reynolds numbers on heat transfer and fluid flow characteristics in a square shaped microchannel heat exchanger (MCHE) is numerically investigated in this study. The performance of an aluminum MCHE with four different types of nanofluids (aluminum oxide (Al2O3), silicon dioxide (SiO2), silver (Ag), and titanium dioxide (TiO2)), with three different nanoparticle volume fractions of 2%, 5% and 10% using water as base fluid is comprehensively analyzed. The three-dimensional steady, laminar developing flow and conjugate heat transfer governing equations of a balanced MCHE are solved using the finite volume method. The MCHE performance is evaluated in terms of temperature profile, heat transfer rate, heat transfer coefficient, pressure drop, wall shear stress pumping power, effectiveness, and overall performance index. The results reveal that nanofluids can enhance the thermal properties and performance of the heat exchanger while having a slight increase in pressure drop. It was also found that increasing the Reynolds number causes the pumping power to increase and the effectiveness to decrease. 2010 Elsevier Ltd.